An Interprofessional Approach to Assessing Research Ethics Capacity in Vietnam: Implications for Nursing Education. Issue 3 (26th May 2021) - Upvall, Michele; Thao, Nguyen Thanh; Beever, Jonathan; Huy, Nguyen Vu Quoc
Abstract: This study assessed the knowledge, practices, attitudes, and educational needs related to research ethics across health professions faculty, including nursing, in a university located in Vietnam. Consistent themes across five focus groups and two interviews included promoting knowledge of research ethics, ethics in context, and the value of international partnerships to promote ongoing knowledge of research ethics. Results from this study can be used to strengthen the university's curriculum reform efforts for nursing programs and other health profession curricula across the university. Research partnership opportunities may further the development of research ethics among nursing faculty and students.